(untitled) (Research, Society and Development, 2020)
The purpose of this research was to describe the knowledge of elementary school teachers about attention deficit hyperactivity disorder and how to manage the disorder in the school environment. This is an exploratory-descriptive qualitative approach research, which took place in a primary and secondary school in a city in the interior of the state of Rio Grande do Sul. Eight teachers from the first four grades of elementary school were interviewed, morning and afternoon school shifts. The data revealed that teachers in their academic life sporadically address this theme; that they are more concerned with solving the pedagogical situations that arise as a result of the disorders students may have than seeking help from health professionals; they also reported the difficulty of acceptance and misunderstanding of parents regarding the disorders, leaving the teacher and school the solution of the problem. We conclude from our study that support and joint work are necessary for a more accurate diagnosis, determining the direct intervention for the treatment of the disease. Since the earlier the start of treatment the better the quality of life of this individual.